Analysis of Civil Servant Performance in Population Administration Services at the Mallusetasi Sub-District Office Barru Regency - Rosdiana, Rosdiana (LPPPIPublishing, 2024)
This study aims to determine the performance of civil servants (PNS) in population administration services at the Mallusetasi Sub-District Office, Barru Regency. The study utilizes the following indicators: a. Quality, b. Quantity, c. Timeliness, d. Effectiveness. Furthermore, to identify the factors influencing PNS performance in population administration services at the Mallusetasi Sub-District Office, Barru Regency, the following indicators are employed: a. Effectiveness and efficiency, b. Authority and responsibility, c. Discipline, and d. Initiative. Data sources were obtained through observation, documentation, and interviews. The research type employed is qualitative. The results of this study indicate that the performance of Civil Servants (PNS) in population administration services at the Mallusetasi Sub-District Office, Barru Regency, is satisfactory. Moreover, based on the research indicators: effectiveness and efficiency, authority and responsibility, discipline, and initiative, it is concluded that these indicators influence the performance of Civil Servants (PNS) in population administration services at the Mallusetasi Sub-District Office, Barru Regency.